Longitudinal impact of clinical and socioenvironmental variables on oral health-related quality of life in adolescents - Janice Simpson PAULA; José Nilton da CRUZ; Thiago Gentil RAMIRES; Edwin Moysés Marco ORTEGA; Fábio Luiz MIALHE (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of the present study was to investigate the impact of oral diseases, socioeconomic status, and family environmental factors on changes in the perception of oral health-related quality of life (OHRQoL) in adolescents. A prospective cohort study was conducted in Juiz de Fora, Minas Gerais, Brazil, with a sample of 286 twelve-year-old adolescents from public and private schools, selected by means of multistage random sampling. The adolescents were clinically examined for dental caries experience (number of decayed, missing, and filled teeth - DMFT index), presence of bleeding, and orthodontic treatment needs. They were asked to complete the Brazilian version of the Child Perceptions Questionnaire (CPQ11-14). In addition, parents answered a questionnaire about their socioeconomic status and family environmental characteristics. After 3 years, the adolescents were contacted again to participate in the research. Logistic regression models, with explanatory variables assessed both individually and jointly, were used to determine which independent variables impacted longitudinally on OHRQoL. The final result demonstrated that only DMFT explained part of the response variability in CPQ11-14 scores. In conclusion, caries experience was an important predictor of OHRQoL in adolescents followed up for 3 years.